Strategic impacts of technology switch-over: Who benefits from electronic commerce? - Martin Bandulet (Universität Augsburg, Institut für Volkswirtschaftslehre, 2002)
The introduction of new digital production and distribution technologies may alter the firms' strategy sets, as they are not able to commit credibly to quantity strategies anymore. Mixed oligopoly markets may emerge where some companies compete in prices, while others adjust their quantities. Using an approach first published by Reinhard Selten (1971) and developed further by Richard Cornes and Roger Hartley (2001), I calculate the Nash equilibrium of such an N-person game in a linear specification. Then I discuss the strategic effect of a technology switch-over on market performance and social welfare. A firm that introduces new technology suffers a srategic disadvantage, while consumers benefit.
urn:nbn:de:bvb:384-opus4-712408
Keywords: D43; L13; 330; electronic commerce; oligopoly theory; product differentiation